2022
DOI: 10.51329/mehdiophthal1440
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-acute ocular manifestations in pediatric patients with COVID-19: A systematic review

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has been the most challenging health problem in the last 2 years. Post-COVID-19 multisystem inflammatory syndrome of children (MIS-C) is a severe post-COVID-19 complication in pediatric patients. Ocular manifestations may be the first presentation of MIS-C, wherein prompt treatment may improve outcomes. In this systematic review, we aimed to summarize the acute and sub-acute ocular manifestations in pediatric patients with laboratory-confirmed COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ocular manifestations of COVID-19 infection in children are variable, and the prevalence ranges from 0.7% to 31.6% in children worldwide [ 11 , 12 , 13 , 14 ]. They may resolve spontaneously or be the first signs of a severe infection, especially in MIS-C, where accelerated treatment may improve the prognosis [ 15 ]. Ocular manifestations so far reported and documented in the course of COVID-19 in children include conjunctivitis, chorioretinitis and/or retinal vasculitis, epitheliitis, corneal epitheliopathy, orbital cellulitis, orbital inflammatory disease, lacrimal gland inflammation, retinal vascular obstruction, retinopathy, maculopathy, intraocular inflammation, cranial nerve palsy and optic neuritis [ 6 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular manifestations of COVID-19 infection in children are variable, and the prevalence ranges from 0.7% to 31.6% in children worldwide [ 11 , 12 , 13 , 14 ]. They may resolve spontaneously or be the first signs of a severe infection, especially in MIS-C, where accelerated treatment may improve the prognosis [ 15 ]. Ocular manifestations so far reported and documented in the course of COVID-19 in children include conjunctivitis, chorioretinitis and/or retinal vasculitis, epitheliitis, corneal epitheliopathy, orbital cellulitis, orbital inflammatory disease, lacrimal gland inflammation, retinal vascular obstruction, retinopathy, maculopathy, intraocular inflammation, cranial nerve palsy and optic neuritis [ 6 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular involvement is not uncommon and various ophthalmic manifestations have been reported 1 , 2 . Anterior segment manifestations include conjunctival congestion, conjunctivitis, severe keratitis, and acute angle closure; uveal manifestations include anterior uveitis, panuveitis, reactivation of uveitis, retinal vasculitis, and chorioretinitis; retinal manifestations include microangiopathy, cotton wool spots, hemorrhages, central serous retinopathy, central retinal artery/vein occlusion, and Purtscher-like retinopathy; neuro-ophthalmic manifestations include optic neuritis, extraocular muscle palsies, and benign idiopathic intracranial hypertension with papilloedema; and orbital includes mucomycosis 1 6 . COVID-19 affects the retina possibly through viral invasion or immune-mediated inflammation, even after recovery 7 .…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of COVID-19 in pediatric cases primarily affects the respiratory system similar to those observed in adults, it has been associated with a range of systemic manifestations, including ocular involvement. Notably, conjunctivitis was the most frequent ocular manifestation in children with acute, sub-acute, or post-COVID-19 multisystem in ammatory syndrome [4]. Regarding posterior segment manifestations, several studies have reported pathological changes in the retina resulting from the in ammatory processes linked to previous or concomitant SARS-CoV-2 infection in the adult population [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%